1998
DOI: 10.1046/j.1523-1747.1998.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

The Human Hair Follicle: A Reservoir of CD40+ B7-Deficient Langerhans Cells that Repopulate Epidermis After UVB Exposure

Abstract: The ability of skin to maintain its protective structural and functional integrity depends on both resident and circulating cells. Until now, it was thought that dendritic antigen presenting cells of epidermis (Langerhans cells) were replaced by circulating bone marrow derived precursors. Here we show by immunostaining studies of timed biopsies taken from human skin after ultraviolet exposure, that hair follicle is a critical reservoir of Langerhans cells that repopulate epidermis depleted of Langerhans cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 28 publications
2
55
0
8
Order By: Relevance
“…Therefore, it is possible to envisage that the capacity to produce haematopoietic cells locally in skin could play a role in, for example, wound healing and immune surveillance. This might be true, especially in view of the recent reports that the hair follicle can serve as an immediate reservoir of Langerhans cells between bone marrow and epidermis (Gilliam et al, 1998). By contrast, if it turns out that the follicle harbors a few multi-potent stem cells, then the effects that we have observed could be just a manifestation of the different environmental conditions that these cells are being put into.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, it is possible to envisage that the capacity to produce haematopoietic cells locally in skin could play a role in, for example, wound healing and immune surveillance. This might be true, especially in view of the recent reports that the hair follicle can serve as an immediate reservoir of Langerhans cells between bone marrow and epidermis (Gilliam et al, 1998). By contrast, if it turns out that the follicle harbors a few multi-potent stem cells, then the effects that we have observed could be just a manifestation of the different environmental conditions that these cells are being put into.…”
Section: Discussionmentioning
confidence: 72%
“…There is growing interest in hair follicle immunology and evidence that the follicle has a unique immunological profile (Paus et al, 1999;Gilliam et al, 1998;Westgate et al, 1991). Therefore, it is possible to envisage that the capacity to produce haematopoietic cells locally in skin could play a role in, for example, wound healing and immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…The bulge region of the hair follicle serves as a niche for keratinocytes, melanocytes, and mast-cell progenitors, and there is evidence suggesting that, after epidermal injuries, LCs can be repopulated from the follicles alone. 98 Conditional depletion of LCs and careful monitoring of their repopulation should help to resolve these issues. In contrast, in inflamed settings, LCs are replaced by circulating Gr-1 hi monocytes in a M-CSFR-dependent manner.…”
Section: The Lc Exceptionmentioning
confidence: 99%
“…While analyzing baboon skin by in situ hybridization, Rock et al (1997) reported the presence of Ga15 in hair follicular epithelium. In the hair follicle bulge of murine skin (Shi et al 2003) reside CD34-positive cells that may serve as a reservoir for Langerhans cells as well as for other immune cell precursors (Gilliam et al 1998, Kumamoto et al 2003. The existence of a population of slowly cycling immature cells originated from hematopoietic precursors could thus explain the presence of Ga15 signal.…”
Section: Epitheliamentioning
confidence: 99%